2017
DOI: 10.1103/physrevd.95.025003
|View full text |Cite
|
Sign up to set email alerts
|

Scattering in a three-dimensional fuzzy space

Abstract: We develop scattering theory in a non-commutative space defined by a su(2) coordinate algebra. By introducing a positive operator valued measure as a replacement for strong position measurements, we are able to derive explicit expressions for the probability current, differential and total cross-sections. We show that at low incident energies the kinematics of these expressions is identical to that of commutative scattering theory. The consequences of spacial non-commutativity are found to be more pronounced a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The noncommutative quantum mechanics on three-dimensional fuzzy space has been studied extensively in Refs. [8,[14][15][16]. In these studies it was shown that this formulation reduces to commutative quantum mechanics in the commutative limit and that it is a realistic description of the physics at low energies.…”
Section: Three-dimensional Fuzzy Spacementioning
confidence: 99%
“…The noncommutative quantum mechanics on three-dimensional fuzzy space has been studied extensively in Refs. [8,[14][15][16]. In these studies it was shown that this formulation reduces to commutative quantum mechanics in the commutative limit and that it is a realistic description of the physics at low energies.…”
Section: Three-dimensional Fuzzy Spacementioning
confidence: 99%
“…In this section we study the modified classical dynamics on three dimensional fuzzy space. The non-commutative quantum mechanics on three dimensional fuzzy space has been studied extensively in [8,[14][15][16]. In these studies it was shown that this formulation reduces to commutative quantum mechanics in the commutative limit and that it is a realistic description of the physics at low energies.…”
Section: Three Dimensional Fuzzy Spacementioning
confidence: 99%
“…for the space-time commutation relations is normally adopted, where θ µν are constants. Generalizations to fuzzy-and Snyder-space have been explored in [9][10][11][12] and [13] respectively. The latter offers the possibility of avoiding the breaking of rotational and Lorentz symmetries.…”
Section: Introductionmentioning
confidence: 99%